Phosphorus quantification in soil using LIBS assisted by laser-induced fluorescence - Shweta Soni; Jan Viljanen; Risto Uusitalo; Pavel Veis (Heliyon, 2023)
Quantification and monitoring of phosphorus in soil plays a critical role in environmentally friendly agriculture, especially in mitigation of phosphorus leakages to water systems and subsequent risk for eutrophication. On the other hand, deficiency in phosphorus would lead to problems in development and growth of cultivated crops. Therefore, monitoring and quantification of phosphorus status in soil is essential. In this work, laser-induced breakdown spectroscopy assisted by laser-induced fluorescence (LIBS-LIF) is introduced for quantification of readily soluble phosphorus in soil and compared to the analytical performance of the conventional LIBS method. Mineral soils with variable phosphorus status were used for the analysis. The calibration curves are plotted to evaluate the detection limit of the soluble phosphorus. Compared results demonstrate improvement in detection limit from 3.74 mg/kg to 0.12 mg/kg for clay soil and from 10.94 mg/kg to 0.27 mg/kg for silt loam/loam soil in LIBS and LIBS-LIF measurements, respectively. For the LIBS-LIF measurement, detection limits are comparable with established chemical soil analyses. The proposed method would substantially reduce required sample preparation and laboratory work compared with conventional phosphorus quantification. In addition, as the calibration curves demonstrate that the calibration for soluble phosphorus holds within a soil type, LIBS-LIF has the potential to be used for high throughput soil analysis.